Analysis of Ta’alluq Potential in Murabahah Bil Wakalah Scheme (BTN Syariah Solo) - Royyan Ramdhani Djayusman; Inna Putri Istiqomah; Difa’ul Haq Azuha (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
In the Islamic financial industry, compliance with Sharia principles is a key factor in maintaining public trust and ensuring the legitimacy of financial products. One of the challenges that arises is the implementation of multi-contract transactions, such as in the execution of the murabahah bil wakalah contract at Bank BTN Syariah KCP Solo. The purpose of the research is to analyze Sharia compliance in the practice of murabahah bil wakalah financing at Islamic banks, specifically at Bank BTN Syariah KCP Solo. The murabahah bil wakalah financing involves two contracts: the wakalah contract and the murabahah contract, which are interrelated, even though they are formally separate. This study will explore how the Islamic bank ensures that both contracts comply with Sharia rules, particularly in terms of the separation of the contracts. The study also discusses the potential occurrence of ta’alluq that may arise due to the interdependence between the wakalah and murabahah contracts, as well as its impact on the freedom of customers in their choice. The research method used in this study is qualitative descriptive, and the data are analysed using thematic analysis. The findings show that, although the wakalah and murabahah contracts are formally separated, they remain substantively connected in supporting a shared objective. This study identifies challenges in ensuring Sharia compliance. It provides recommendations for Islamic banks to maintain the integrity of Sharia products by prioritizing transparency, fairness, and customer freedom in every transaction.